The Wild Theory of Nicolaus Copernicus - Yulia Zahra (ADALAH, 2019)
Heliocentrism is one of the controversial theory which was found by Nicolaus Copernicus. This theory described that the Sun is the center of the universe and it was opposed to geocentrism, which placed the Earth at the center. This theory is contrary to the principles of the church and the contents of the Bible at that time. Some scientists oppose the formulation of Nicolaus Copernicus because it contradicts the principles of the church. Although he was in good standing with the Church. At this time, Copernicus was praised by many as the Father of Modern Astronomy. Indeed, his description of the universe was purified and improved by later scientists, such as Galileo, Kepler, and Newton. The controversy of the theory that was sparked by him made us aware of the fragility of scientific concepts that have been accepted for a long time. Through research, observation, and mathematics, Copernicus overturned a scientific and church concept that was rooted but was mistaken that the center of the solar system was the earth, an incorrect concept.Keywords: heliocentrism, the principles of the church, controversyAbstrakHeliosentrisme adalah salah satu teori kontroversial yang ditemukan oleh Nicolaus Copernicus. Teori ini menggambarkan bahwa matahari adalah pusat di alam semesta dan ia menentang geosentrisme, yang menempatkan bumi di tengah. Teori ini bertentangan dengan prinsip-prinsip gereja dan isi Alkitab pada waktu itu. Beberapa ilmuwan menentang perumusan Nicolaus Copernicus karena bertentangan dengan prinsip-prinsip gereja. Meskipun dia dalam posisi yang baik dengan gereja. Pada saat ini, Copernicus dipuji oleh banyak orang sebagai Bapak Astronomi Modern. Memang, uraiannya tentang alam semesta dimurnikan dan ditingkatkan oleh para ilmuwan kemudian, seperti Galileo, Kepler, dan Newton. Kontroversi teori yang dipicu olehnya membuat kita sadar akan kerapuhan konsep-konsep ilmiah yang telah diterima sejak lama. Melalui penelitian, pengamatan, dan matematika, Copernicus menjungkirbalikkan konsep ilmiah dan gereja yang berakar tetapi keliru bahwa pusat tata surya adalah bumi, sebuah konsep yang salah.Kata kunci: heliosentrisme, prinsip-prinsip gereja, kontroversi